Electronic word of mouth (eWOM): Effects of comments in Facebook towards customer booking intention / Nurul 'ain Zulkifli, Nurul Azwani Mohd Lazim and Fatin Humaira' Zulkifli - Zulkifli, Nurul 'ain; Mohd Lazim, Nurul Azwani; Zulkifli, Fatin Humaira' (2016)
Electronic word of mouth (eWOM) is increasingly used by the consumers to make review or comments about the product or services through posted on a website or social media such as Facebook. Thus, the main objective of this research is to determine the effect of comment posted on Facebook towards customer hotel, restaurant and attraction booking intention in Melaka. A total of 200 self-administered questionnaires were distributed to the tourists and visitors around Bandar Hilir, Melaka, Malaysia. The data were analysed by using the SPSS 18.0. The outcomes of this research project will help operators of hotel, restaurant and attraction in having a better explanation and understanding the factors that motivates customers booking intention. Besides that, it is hopefully that this research can increase the operators of hotel, restaurant and attraction level of awareness towards online reviews or comments posted made by customers through Facebook. This research also indirectly will educate public and also increase their level of awareness.